Eugenol-Derived N-(3-aminopropyl)-2-(4-allyl-2-methoxyphenoxy)acetamide as a Selective Receptor for Cyanide and Dihydrogen Phosphate: Spectroscopic and Computational Insights - Venty Suryanti; Laras Ayu Wijayanti; Yoga Royandana Firdaus; Fajar Rakhman Wibowo; Ahmad Marzuki (Journal of Multidisciplinary Applied Natural Science, 2026)
The compound N-(3-aminopropyl)-2-(4-allyl-2-methoxyphenoxy)acetamide (4) was synthesized from eugenol through a three-step reaction. Possessing both amide and amine groups, the molecule provides effective hydrogen-bond donor sites suitable for anion recognition. The binding behaviour of compound 4 toward F⁻, CN⁻, AcO⁻, SO₄²⁻, and H₂PO₄⁻ was examined using 1H-NMR spectroscopy. No significant spectral changes were observed upon addition of F⁻, AcO⁻, or SO₄²⁻, indicating minimal or no interaction. In contrast, the introduction of CN⁻ and H₂PO₄⁻ produced notable chemical shift variations, consistent with hydrogen-bond formation and host-guest complexation. To further elucidate these interactions, density functional theory (DFT) calculations were performed at the aug-cc-pVDZ level. Computational models revealed that F⁻ and AcO⁻ induce cleavage of the amide N–H bond through strong hydrogen bonding and partial covalent character, whereas CN⁻ and H₂PO₄⁻ primarily engage in hydrogen-bonding interactions without bond cleavage. Gauge-independent atomic orbital (GIAO) calculations predicted substantial downfield shifts of the amide proton, from 4.72 ppm in the free receptor to 15.5, 10.89, 16.54, and 12.27 ppm for F⁻, CN⁻, AcO⁻, and H₂PO₄⁻, respectively. Overall, both experimental and computational findings demonstrate that compound 4 functions as an effective receptor for CN⁻ and H₂PO₄⁻, with strong theoretical binding responses also observed for F⁻ and AcO⁻.